Perbandingan Savings Algorithm dengan Nearest Neighbour dalam Menyelesaikan Russian TSP Instances - Sanggala, Ekra; Bisma, Muhammad Ardhya (Universitas Suryakancana, 2023)
Travelling Salesman Problem (TSP) is the problem for finding the shortest route starting from start node then visiting number of nodes exactly once and finally go back to start node. Several heuristics are popular for solving TSP, for example Savings Algorithm and Nearest Neighbour. Performance heuristics on solving TSP are diverse, so there is need of reference for choosing a heuristic. Comparing heuristics on solving instance can be a reference for choosing a heuristic. This paper will discuss about comparison Savings Algorithm and Nearest Neighbour on Solving Russian TSP Instances. For generating length of route, Savings Algorithm is better than Nearest Neighbour, while for generating CPU time, Nearest Neighbour is better than Savings Algorithm.Â Travelling Salesman Problem (TSP) merupakan permasalahan penentuan rute terpendek yang diawali dari titik start untuk mengunjungi sekumpulan titik tepat sekali dan diakhiri dengan kembali ke titik start. Beberapa Heuristik yang cukup populer untuk menyelesaikan TSP antara lain Savings Algorithm dan Â Nearest Neighbour. Kemampuan Heuristik dalam menyelesaikan TSP berbeda-beda, sehingga diperlukan sebuah acuan untuk menentukan Heuristik yang akan digunakan. Membandingkan Heuristik dalam menyelesaikan instance dapat menjadi acuan untuk pemilihan Heuristik. Pada paper ini akan dibahas mengenai perbandingan Savings Algorithm dan Nearest Neighbour dalam menyelesaikan Russian TSP Instances. Untuk panjang rute yang dihasilkan, maka Savings Algorithm lebih baik dibandingkan Nearest Neighbour, sedangkan untuk CPU Time Â yang dihasilkan, maka Nearest Neighbour lebih baik dibandingkan Savings Algorithm.